Further Studies on the Frequency and Length of the Glandulo-Metaplastic Esophageal Mucosa in Baboons - RUBIO, C.A. (2009)
BACKGROUND: In previous studies, the length of the glandulo-metaplastic esophageal mucosa (GMEM) at the gastroesophageal junction was assessed in a selected group of baboons. In this study, the length of the GMEM was measured in the entire esophagus in a cohort of unselected adult baboons. MATERIALS AND METHODS: In 15 female baboons, the entire esophagus was removed en bloc at autopsy, from the tongue to the angle of His. No part of the stomach was included. The length of GMEM was measured using a calibrated ocular microscale. RESULTS: GMEM was found in 11 out of the 15 esophagi. The total length of GMEM recorded in the 11 cases was 115 mm (mean 10.5 mm, range 1–45 mm). The mean age for animals with GMEM was 15.5 years (range 7–32 years) and for animals without GMEM was 14.0 years (range 7–20 years); the difference was non-significant (p<0.6). No significant association was found between the length of the GMEM and the age of the animals (p<0.6). CONCLUSION: This study substantiates the notion that GMEM in baboons is a postnatal physiological adaptative process of the esophageal mucosa to daily regurgitation with rumination of gastric juices of low pH. The GMEM apparently progresses upwards, along the esophageal mucosa. The baboon might be an excellent animal model to study the series of histological events that take place in the distal esophagus under the influence of protracted gastroesophageal reflux.